Is the Endangered Species Act living to its full potential? The reassessment of the conservation status and recovery of Macbridea alba Chapm. as a case study - Johnson, Sara Ann; Molano-Flores, Brenda (Frontiers in Conservation Science, 2023)
Since 1988, the Cooperative Endangered Species Conservation Fund or “Section 6” fund facilitates partnerships between the U.S. Fish and Wildlife Service and state agencies that aim to provide data pertinent to the recovery of Endangered Species Act (ESA) protected species. Despite the success of these efforts, research for rare plants is chronically underfunded and many species experience long periods of research inactivity that hinders their conservation. One example is Macbridea alba Chapm. (white birds-in-a-nest, Lamiaceae, M. alba from hereon), a federally threatened and state endangered mint endemic to four counties within the Florida panhandle. The species is a candidate for delisting after 30 years of protection under the ESA, however a lack of up-to-date data associated with the species has continually challenged the implementation of effective conservation programs and prolonged the recovery process. The focus of this paper is to review the timeline of recovery goals for M. alba, present a summary of recent research findings (i.e., species distribution models, habitat associations, reproductive ecology), and identify achievements as well as persistent obstacles to recovery and delisting. Our research focused on 5 of 10 recovery actions listed in the recovery plan for M. alba. Our findings provide updated data and make novel contributions to the protection of M. alba that will prioritize and improve management efforts. Overall, our work highlights frequent barriers to the recovery and delisting of rare species, using an endemic plant species as a case-study. Importantly, we outline effective methods for the rapid assessment of at-risk plant species that due to enduring data gaps, face an uncertain future in listing and recovery. We hope our work provides a convincing case demonstrating the critical need for current and expanded ESA funding and encourages a diversity of individuals and institutions to participate in critical rare plant research to swiftly fill research gaps and expedite recovery of some of the rarest plant species across the United States.